Micro-flow visualization of in vitro blood through a microchannel with a bifurcation and confluence - Cidre, Diana (2011)
Micro-visualization techniques have been used to investigate the in vitro blood flow through straight glass capillaries. Although the glass microchannels present certain similarities to in vivo microcirculation, it is also clear that these kind of in vitro experiments differ from microvessels in several respects, such as: elasticity of microvessels, effect of the endothelial surface layer and microvascular networks composed with short irregular vessel segments which are linked by numerous bifurcations and convergences. Thus it was not surprising that several studies on blood flow in glass microtubes and in microvessels have yielded conflicting results with respect to blood viscosity and flow resistance. The main purpose of this work is to improve our understanding about the effect of a bifurcation and convergence on the rheological properties of in vitro blood. The microchannel containing a bifurcation and confluence will be fabricated in PDMS by using a soft lithography technique. The flow behaviour of both pure water (PW) and dextran 40 (Dx40) containing about 14% (14Hct) of human red blood cells (RBCs) will be investigated by means of a confocal micro-PTV system. Additionally, the experimental measurements obtained with PW will be also compared numerically by using the commercial finite element software package POLYFLOW®.